Gaya Kepemimpinan Adaptif Sri Mulyani Indrawati dalam Pengelolaan Krisis Ekonomi Indonesia - Weri Zaitul Amnah; Syofia Afni; Wulandari Septiyan Ningsih; Yulia Hanoselina; Rizki Syafril (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research examines Sri Mulyani Indrawati's adaptive leadership style in managing economic crises in Indonesia. Given the importance of effective responses to complex economic challenges, this study aims to analyze the characteristics of adaptive leadership applied in addressing the 2008-2009 global economic crisis, the COVID- 19 pandemic, and post-pandemic challenges. The research method employed is qualitative with a literature study approach. The analysis process involves collecting various literature sources, with scholarly journals and articles as primary references for obtaining information. The findings indicate that Sri Mulyani's adaptive leadership style is characterized by strong analytical skills, policy flexibility, data-driven decision-making, transparent communication, and the courage to implement structural reforms. The implication of this research is to provide an in-depth understanding of adaptive leadership in the context of national economic crisis management, which can serve as a reference for developing leadership models in the public sector to address dynamic economic challenges